Legal Protection Efforts for Victims of Sexual Violence Crimes in Indonesia - Nurahmad, Silvi; Gagarin Akbar, Muhammad Gary; Abas, Muhamad (IHSA Institute, 2025)
Sexual violence, particularly rape, constitutes a serious violation of human rights, inflicting lasting physical, psychological, and social impacts on victims. In 2024, the National Commission on Violence Against Women (Komnas Perempuan) recorded 445,502 cases of sexual violence in Indonesia, emphasizing the urgency for robust legal protection. This study aims to examine the legal protections afforded to rape victims under Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS) and evaluate the challenges in its implementation. Using a normative legal research method, the analysis draws from primary legal sources, notably the UU TPKS, and relevant secondary literature. The findings indicate that the UU TPKS grants victims access to medical services, psychological support, legal assistance, and confidentiality safeguards. However, implementation is hindered by entrenched patriarchal norms, societal stigma, and inadequate sensitivity among law enforcement. The study concludes that strengthening public awareness, improving law enforcement capacity, and adopting restorative justice principles are essential for effective legal protection. This research contributes to the development of a more responsive and victim-centered legal framework in Indonesia.